Sire evaluation of milk producers co-operative union limited of Bangladesh (Bangladesh Journal of Animal Science, 2013)
Data on 3637 cows of seven genetic groups at Baghabarighat milk shed area, from 1991 to 2000 were analyzed. The genetic groups were Pabna Milking (PM) cows, ½PM×½ Sahiwal (PM×SL), ½PM×½Frisian (PM×FN), Australian Friesian Sahiwal (AFS), ½Sahiwal×¼PM×¼ Friesian [SL(PM×FN)], ½Friesian ×¼PM×¼Sahiwal [FN(PM×SL)] and ½Friesian×¼Sahiwal×¼ Jersey [FN(SL×JR)]. The purpose of this study was to predict breeding values (PBV) of dairy sires using individual daughters performance (birth weight, lactation yield, fat% and SNF%) records at Baghabarighat milk shed area. The heritability values were estimated as 0.27±0.05 for birth weight, 0.45±0.03 for lactation yield, 0.37±0.04 for fat% and 0.46±0.01 for SNF%. The high genetic variability of birth weight, lactation yield, fat and SNF% indicates that there is a great opportunity or genetic improvement when these traits are included in a selection scheme. The first 3 top sires were 24, 14 and 20 for birth weight; sire number 19, 36 and 23 for lactation yield; sire number 16, 11 and 26 for fat % and sire number 14, 19 and 16 for SNF% were ranked on the basis of PBV.DOI: http://dx.doi.org/10.3329/bjas.v41i2.14104Bang. J. Anim. Sci. 2012. 41 (2): 74-78